2013
DOI: 10.1007/s11605-013-2287-1
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid at Low pH Reduces Squamous Differentiation and Activates EGFR Signaling in Esophageal Squamous Cells in 3-D Culture

Abstract: In this study, we expanded our previous work using an immortalized primary esophageal squamous cell line (EPC1). We demonstrate that EPC1 cells form a multi-layer, stratified epithelium when grown on polyester transwell filters in media supplemented with calcium. When exposed to short pulses of bile and pH 5, but not either condition alone, EPC1 cells demonstrate a reduction in stratification layers and reduced expression of squamous epithelium-specific genes. Bile at pH 5 also causes activation of epidermal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…We have demonstrated that bile acids induce intracellular acidosis in EECs and their effect was more pronounced under the acidic condition, in accordance with previous findings in Barrett's-derived and normal esophageal cell lines (15). The administered mixture of bile acids was designed to mimic the bile acid composition of the refluxate under pathophysiological conditions (12,26,32). In accordance with the previous observations on mouse EECs only DC was shown to induce acidification at neutral conditions and had the greatest effect at acidic pH among the seven bile acids investigated (71).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We have demonstrated that bile acids induce intracellular acidosis in EECs and their effect was more pronounced under the acidic condition, in accordance with previous findings in Barrett's-derived and normal esophageal cell lines (15). The administered mixture of bile acids was designed to mimic the bile acid composition of the refluxate under pathophysiological conditions (12,26,32). In accordance with the previous observations on mouse EECs only DC was shown to induce acidification at neutral conditions and had the greatest effect at acidic pH among the seven bile acids investigated (71).…”
Section: Discussionsupporting
confidence: 85%
“…Bile acids induce an intracellular acidification in CP-A cells. To mimic the pathophysiological conditions in GERD, BAC was prepared using a mixture of seven bile acids, as described in MATERIALS AND METHODS (12). The effect of BAC on the pH i of CP-A cells was tested under acidic (pH 5.5) and neutral (pH 7.5) conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…most proximally, whereas bile acids are insoluble and therefore incapable of forming micelles at lower pH ranges in the distal esophagus 31,32 . In vitro studies have shown that solubilized duodenal bile salts are a strong inducer of CDX2 expression and goblet cell differentiation [33][34][35] . The pH gradient along the BE segment could therefore create a proximal-distal gradient of bile salt solubility, which could determine the relative proportion of specific gland phenotypes along the length of the esophagus.…”
Section: Studies Of Bile Salt Solubility Found It To Be Greatest At Imentioning
confidence: 99%
“…The mechanism(s) by which bile and various bile acids (BA) may cause intestinal metaplasia has yet to be elucidated. While bile has been shown to reduce squamous differentiation in primary esophageal cell lines ( 12 , 13 ), one of the major questions remains which of the BA/salts are the more potent inducers of epithelial metaplasia in the esophagus in vivo ? Bile salts are formed in the liver by conjugating BA – cholic acid (CA) and chenodeoxycholic acid (CDCA) – with taurine (pKa 2) and glycine (pKa 3.7) to form tauroconjugates (TC) and glycoconjugates (GC), respectively.…”
Section: Bile Salts Vs Bile Acids: Which Are Likely the More Potent mentioning
confidence: 99%